“Corioamnionitis en primigesta juvenil con embarazo de 33 semanas” - Guerrero Terán, José Luis (2019)
Chorioamnionitis is a pathology difficult to diagnose accurately, so it implies a problem for health professionals who are exposed to its management. Not only does it produce alterations in the usual course of the pregnancies but it also causes high morbidity and mortality in the "RN". The present work indicates in a General way the physiopathology, the clinical and paraclinical findings of the disease and its management. The clinical point is one of the main points of view for the diagnosis of chorioamnionitis. Given the pathology, it is essential that labor occurs, regardless of the weeks of gestation that the patient has, will apply to the pregnant woman antibiotics, from the moment of diagnosis. This forms the basis of the treatment and the future of the pregnant woman.